THE INFLUENCE OF Ficus carica AND Averhoa blimbi L. WATER BATH ON FREE RADICAL AND PROTEIN LEVEL OF GAMMA RADIATION EXPOSED-BEEF - Maghfiroh, Lailatul; Fitrainingsih, Avin Ainur (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.612, 2017)
Ionizing radiation has been used in various technologies. One example of its use in industry is food preservation process.Ionizing radiation is able to kill microorganism. However, it also causes free radicals. Beef exposed with gamma radiation from Cobalt 60 will be ionized and its tissue will be damaged due to free radicals. The damage also can occur on its protein. It needs antioxidant to prevent the free radicals. The study aims to find out the influence of gamma radiation on beef before and after adding the antioxidant. Antioxidant used is water bath of Ficus carica and Averhoa blimbi. Then the beef sample is tested its free radicals using ESR. The result shows that when added with antioxidant the amount of free radical decreases for 77.46%. It is due to the fact that Ficus carica and Averhoa blimbi contain flavonoid compound, vitamin C, tannin, saponin, and beta-carotenewhich act as antioxidant. Then the protein content is tested using kjehdahl method. The result shows that the protein level in the beef is 21.03% and when the beef is exposed to gamma ray it decreases to 20.53%. When antioxidant is added, the protein level is 19.81% and 19.06%.